Using XML Schemas effectively in WSDL Design achieve a higher degree of portability with these best practices. - Peltz, Chris
Developers are beginning to develop more sophisticated Web services, exchanging complex XML documents rather than simple parameter types. As this shift takes place, development teams begin to grapple with different approaches to designing these Web services interfaces through the use of WDSL. As we've worked with a number of these teams, we've begun to discover some important best practices that can be applied particularly in the use of XML Schemas in a Web services design.